Characteristics, sources and evolution of fine aerosol (PM1) at urban, coastal and forest background sites in Lithuania. (January 2017) - Masalaite, A.; Holzinger, R.; Remeikis, V.; Röckmann, T.; Dusek, U.
Abstract: The chemical and isotopic composition of organic aerosol (OA) samples collected on PM1 filters was determined as a function of desorption temperature to investigate the main sources of organic carbon and the effects of photochemical processing on atmospheric aerosol. The filter samples were collected at an urban (54°38′ N, 25°18′ E), coastal (55°55′ N, 21°00′ E) and forest (55°27′ N, 26°00' E) site in Lithuania in March 2013. They can be interpreted as winter-time samples because the monthly averaged temperature was −4 °C. The detailed chemical composition of organic compounds was analysed with a thermal desorption PTR-MS. The mass concentration of organic aerosol at the forest site was roughly by a factor of 30 lower than at the urban and coastal site. This fact could be an indication that in this cold month the biogenic secondary organic aerosol (SOA) formation was very low. Moreover, the organic aerosol collected at the forest site was more refractory and contained a larger fraction of heavy molecules with m/z > 200. The isotopic composition of the aerosol was used to differentiate the two main sources of organic aerosol in winter, i.e. biomass burning (BB) and fossil fuel (FF) combustion. Organic aerosol from biomass burning is enriched in 13 C compared to OA from fossil fuel emissions. δ 13 COC values of the OA samples showed a positive correlation with the mass fraction of several individual organic compounds. Most of these organic compounds contained nitrogen indicating that organic nitrogen compounds formed during the combustion of biomass may be indicative of BB. Other compounds that showed negative correlations with δ 13 COC were possibly indicative of FF. These compounds included heavy hydrocarbons and were on the average less oxidized than the bulk organic carbon. The correlation of δ 13 COC and the O/C ratio was positive at low but negative at high desorption temperatures at the forest site. We propose that this might be due to photochemical processing of OA. This processing can lead to accumulation of carbon in the more refractory organic fraction that is depleted in 13 C compared with the less refractory organic fraction. Detailed laboratory experiments are necessary to further investigate the aging of aerosol particles before firm conclusions can be drawn. Graphical abstract: Highlights: Photochemical processing of organic aerosol at the forest site. δ 13 C of organic aerosol provided insight into sources.